Interactive Android Module Development Containing Three Chemical Representation Levels on Material of Salt Hydrolysis - Muhammad Zamhari; Pandu Ridzaniyanto; Tawatchai Kangkamano (Universitas Muhammadiyah Surakarta, 2022)
Three chemical representation is an important aspect of chemistry learning. However, the database study shows that interactive chemistry learning media containing three levels of representation is not available. This research aims to develop and assess the feasibility of an interactive Android-based learning module for senior high school students containing three chemical representation levels on the material of salt hydrolys-is. The study was conducted using research and development (RnD) method. Stages of research were con-ducted as follows, analysis, development process, product validation and assessment. The Android module was subsequently validated by media and concept experts and then limitedly assessed by five chemistry teachers and ten senior high school students. The instrument used was validated by an instrument expert. The validation results by media and concept experts indicated that the media was valid in terms of media performance and salt hydrolysis material. Based on teachers' and students' assessments, the media received a score of 87.5% and 83.0%, with very good category. It can be concluded that the interactive Android-based learning module containing three chemical representations on the material of salt hydrolysis was successful-ly developed and can be tested extensively in senior high school. The developed media closed a significant gap in the need of interactive chemistry learning media containing three levels of chemical representation, especially in the material of salt hydrolisis